2017
DOI: 10.1016/j.celrep.2017.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Metabolic Reprogramming by Influenza Infection for Therapeutic Intervention

Abstract: Summary Influenza is a worldwide health and financial burden posing a significant risk to the immune-compromised, obese, diabetic, elderly, and pediatric populations. We identified increases in glucose metabolism in the lungs of pediatric patients infected with respiratory pathogens. Using quantitative mass spectrometry we found metabolic changes occurring after influenza infection in primary human respiratory cells, and validated infection-associated increases in c-Myc, glycolysis, and glutaminolysis. We conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(201 citation statements)
references
References 37 publications
11
186
3
1
Order By: Relevance
“…Molecular mechanisms through which the virus can control the metabolic pathways have been thoroughly identified. Smallwood et al have shown that an increase in glucose uptake, glycolysis, and glutaminolysis following influenza infection may be related to the loss of PI3K/AKT/mTOR pathway homeostasis and subsequent increase in c-Myc expression in the infected cells [9]. Regarding the available results, the mechanistic target of rapamycin complex 1 (mTORC1) and mTORC2 signaling can be activated by a variety of influenza virus proteins.…”
Section: Glucose Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Molecular mechanisms through which the virus can control the metabolic pathways have been thoroughly identified. Smallwood et al have shown that an increase in glucose uptake, glycolysis, and glutaminolysis following influenza infection may be related to the loss of PI3K/AKT/mTOR pathway homeostasis and subsequent increase in c-Myc expression in the infected cells [9]. Regarding the available results, the mechanistic target of rapamycin complex 1 (mTORC1) and mTORC2 signaling can be activated by a variety of influenza virus proteins.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…The aforementioned metabolic processes are not the only pathways affected by influenza virus infection. This virus has the ability to induce higher consumption rates of glutamine during glutaminolysis, which can be attributed to transient c-Myc overexpression [9]. Myc acts to regulate glutamine uptake and its utilization in the cell [111].…”
Section: Other Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, proteomic analysis on commercially obtained NHBE cells (Lonza) infected with PR8 [281] identified proteins which were associated with host cell defense response, endocytosis and GTPase activity. Influenza virus was also found to increase apoptosis and pyroptosis [282], as well as c-Myc, glycolysis and glutaminolysis in NHBE cells from pediatric patients [283]. Importantly, NHBE cells are also being used for immediate translation of culture tests to clinical uses.…”
Section: Normal Human Bronchial Epithelial Cells (Nhbe)mentioning
confidence: 99%